A halogen-free flame-retardant sponge and its preparation method and application
By using specific raw materials and preparation methods, prepare a halogen -free flame -free sponge with excellent mechanical properties and multi -performance characteristics, solve the problem of insufficient sponge performance in existing technologies, realize higher application performance and market prospects Essence
Patent Information
- Application Number
- CN202411120360.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The existing halogen-free flame-retardant sponges have shortcomings in mechanical properties, water resistance, light resistance and aging resistance, and cannot meet the multi-performance requirements of complex application environments.
Polyether polyol, polyal glycol, polytychenate, modified resin, and modified fillers are used to form a combustible flame -free sponge with excellent mechanical properties and multi -performance characteristics through specific mass ratio and preparation methods.
It significantly improves the mechanical properties, waterproofness, optical resistance and aging resistance of halogen -free flame -retardant sponges, meets the multi -performance needs of the complex application environment, and has excellent market prospects.
Smart Images

Figure BDA0004994896030000181
Abstract
Description
Technical Field
[0001] The present application relates to the field of sponge materials, and in particular to a halogen-free flame-retardant sponge and a preparation method and application thereof. Background Art
[0002] Early flame retardant sponges mainly used halogen-containing chemicals (such as brominated flame retardants) as flame retardant additives, which can effectively improve the flame retardant properties of sponges. Halogen-based flame retardants release hydrogen halide gas when burning, which reacts with free radicals in the flame to interrupt the combustion chain reaction, thereby achieving a flame retardant effect. However, with the increasing awareness of environmental protection and the introduction of relevant laws and regulations, it has become a general trend to reduce the use of toxic and hazardous substances. Therefore, it has become particularly important to develop a sponge product that can meet flame retardant requirements and is environmentally friendly.
[0003] Halogen-free flame retardant sponge is an environmentally friendly material that is widely used in furniture, vehicle interiors, building exteriors, and electronic devices. Compared with traditional flame retardant sponges containing halogens (such as bromides), halogen-free flame retardant sponges do not contain halogens, reducing pollution to the environment and potential harm to human health.
[0004] However, there are also some inherent technical problems in the actual application of halogen-free flame retardant sponge technology. For example, the mechanical properties of halogen-free flame retardant sponge change. The addition of certain halogen-free flame retardants may affect the basic mechanical properties of sponge, such as reducing the toughness, elasticity or tensile properties of sponge, and at the same time, it also needs to face the problem of performance degradation in various aspects caused by the migration of raw materials inside the sponge; on the other hand, with the increase in the fields of existing application products and the more complex use environment, the demand for the performance diversity of sponge is increasing, and the existing sponge products cannot meet the waterproof, light resistance and aging resistance required by complex application environments.
[0005] Therefore, in order to solve the above problems, the present application provides a halogen-free flame retardant sponge and a preparation method thereof. Compared with conventional flame retardant sponges, the halogen-free flame retardant sponge prepared by the present application has better mechanical properties and flame retardancy, and is halogen-free and more environmentally friendly. On the other hand, the halogen-free flame retardant sponge prepared by the present application can effectively improve its waterproofness, light resistance and aging resistance, etc., meet the multi-performance requirements of existing products for halogen-free flame retardant sponges, and has a very excellent market prospect. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a halogen-free flame retardant sponge. The raw materials, calculated by mass, are: 60-80 parts of polyether polyol, 10-20 parts of polypropylene glycol, 40-60 parts of polyisocyanate, 10-25 parts of modified resin, 10-20 parts of modified filler, 2-5 parts of foaming agent, 5-10 parts of flame retardant, 1-3 parts of catalyst, and 5-15 parts of auxiliary agent.
[0007] As a preferred solution, the mass ratio of the polyether polyol, polypropylene glycol and polyisocyanate is (6.5-8): (1.2-1.8): (4.5-5.5).
[0008] As a preferred solution, the mass ratio of the polyether polyol, polypropylene glycol and polyisocyanate is (7-7.5): (1.4-1.6): (4.8-5.4).
[0009] As a preferred solution, the mass ratio of the polyether polyol, the modified resin and the modified filler is (6.5-8): (1.5-2.2): (1.2-1.6).
[0010] As a preferred solution, the mass ratio of the polyether polyol, the modified resin and the modified filler is (7-7.5): (1.8-2): (1.5-1.6).
[0011] As a preferred solution, the polyether polyol is a composition of polyoxypropylene triol and glyceryl polyether triol.
[0012] As a preferred solution, the mass ratio of the polyoxypropylene triol to the glyceryl polyether triol is (5-6):(1-2).
[0013] As a preferred solution, the mass ratio of the polyoxypropylene triol to the glyceryl polyether triol is (5.5-6):(1-1.5).
[0014] As a preferred solution, the weight average molecular weight of the polyether polyol is 2000-6000 g / mol.
[0015] As a preferred solution, the weight average molecular weight of the polyoxypropylene triol is 4000-5000 g / mol.
[0016] As a preferred solution, the weight average molecular weight of the glyceryl polyether triol is 2500-3500 g / mol.
[0017] As a preferred solution, the weight average molecular weight of the polypropylene glycol is 1000-2000 g / mol.
[0018] As a preferred solution, the polyisocyanate is at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and cyclohexane diisocyanate.
[0019] As a preferred solution, the polyisocyanate is a combination of 2,4'-diphenylmethane diisocyanate and cyclohexane diisocyanate.
[0020] As a preferred solution, the mass ratio of the 2,4'-diphenylmethane diisocyanate to cyclohexane diisocyanate is (4-4.5):(0.5-1.5).
[0021] As a preferred solution, the mass ratio of the 2,4'-diphenylmethane diisocyanate to cyclohexane diisocyanate is (4.2-4.4): (0.8-1.2).
[0022] As a preferred solution, the preparation method of the modified resin comprises the following steps: S1: adding glycidyl methacrylate, isooctyl acrylate, dodecyl acrylate and benzophenone into a reaction container, irradiating with a wavelength of 300-450nm under nitrogen for reaction for 1.5-3h, filtering the precipitate after the reaction is completed to obtain a prepolymer; S2: mixing the prepolymer with acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether uniformly and adding them into an acetone solvent, then adding triphenylphosphine and benzoyl peroxide in sequence, and heating to 75-85°C and stirring in a closed manner for reaction for 8-12h to obtain a preproduct; S3: mixing the preproduct with succinic anhydride and a silane coupling agent, maintaining the temperature at 50-60°C for reaction for 2-3h, filtering and washing the product after completion, and vacuum drying to obtain the product.
[0023] As a preferred solution, the mass ratio of glycidyl methacrylate, isooctyl acrylate and dodecyl acrylate is (8-12):(3-4):(2-2.5).
[0024] As a preferred solution, the mass ratio of the prepolymer, acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether is (22-28): (4-6): (1.5-2): (6-8).
[0025] As a preferred solution, the mass ratio of the pre-product, succinic anhydride and silane coupling agent is (8-10): (2-3.5): (0.6-0.9).
[0026] As a preferred solution, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane and vinyltrimethoxysilane.
[0027] The modified resin added in the present application can effectively improve the mechanical, waterproof, light-resistant and aging resistance of the modified resin. The modified resin added in the present application can produce a good cross-linking effect with polyurethane through the various groups it carries, and can act with the modified filler group in the system to become a good carrier, thereby improving the free efficiency of the modified filler in the sponge system, and after the formation of the sponge system, the dispersion effect of the modified filler is greatly enhanced, and the performance degradation problem caused by excessive filler aggregation is avoided; on the other hand, the long molecular chain carried by the modified resin can greatly enhance the steric hindrance of the modified filler when it acts in the sponge system, and the modified filler is effectively guided by the long molecular chain, thereby forming a barrier effect on active molecules and reactive groups, reducing their collision and contact frequency, and thereby obtaining excellent anti-photooxidation, anti-aging and other properties during long-term use.
[0028] As a preferred solution, the preparation method of the modified filler includes the following steps: S1: adding carbon fiber and zinc oxide to a DMF solvent, adding succinic anhydride and 3-aminopropyltriethoxysilane, heating to 60-70°C, and reacting for 3-3.5 hours. After completion, filtering, washing, and taking out the pretreated mixture; S2: adding the pretreated mixture to the DMF solvent again, adding zinc nitrate hexahydrate to form a mixed solution, and then preparing a DMF solution of 2,5-dihydroxyterephthalic acid in another container, heating the reactor to 60-80°C, preferentially adding the DMF solution of 2,5-dihydroxyterephthalic acid, preheating the reactor evenly, and slowly adding the mixed solution, accompanied by stirring at 30-40rpm for 10-15min; S3: sealing the reactor, heating to 130-145°C, stirring at 60-80rpm for 30-42h, cooling naturally to room temperature after the reaction is completed, centrifuging, washing the product with methanol, and vacuum drying at 80-90°C to obtain the product.
[0029] As a preferred solution, the mass ratio of the carbon fiber, zinc oxide, succinic anhydride and 3-aminopropyltriethoxysilane is (3-4): (0.4-0.6): (1.2-1.5): (0.2-0.3).
[0030] As a preferred solution, the mass ratio of the pretreated mixture, zinc nitrate hexahydrate, and 2,5-dihydroxyterephthalic acid is (3-4): (0.6-0.8): (1-1.4).
[0031] As a preferred solution, the mass ratio of the pretreated mixture, zinc nitrate hexahydrate, and 2,5-dihydroxyterephthalic acid is (3.5-3.8): (0.7-0.8): (1.2-1.4).
[0032] As a preferred solution, the average particle size of the zinc oxide is 10 to 25 nm.
[0033] As a preferred solution, the average diameter of the carbon fibers is 4 to 8 μm, and the average length is 0.5 to 1 mm.
[0034] By adding the above modified filler in the present application, the waterproofness, light resistance and aging resistance of the flame retardant sponge can be greatly improved, and the mechanical properties can be enhanced. The modified filler added in the present application can form a composite connection structure with carbon fiber as the main skeleton, which can form a good electron path through surface groups and coordination connection, extend the path of the electron path, and thus obtain a good electron transport effect under light and normal conditions. The existence of this effect can greatly enhance the transport efficiency of the sponge system for charges and electrons, so that the flame retardant sponge obtains excellent antistatic and light resistance.
[0035] On the other hand, the composite structure formed by the modified filler can form a good spreading effect in the sponge system with the carbon fiber plane as the main body, thereby enhancing the dispersion uniformity and stability of the composite filler in the sponge, and can strengthen the intermolecular force between it and the sponge polymer matrix through the connection of surface groups, thereby playing a good connection role when external forces act. In addition, the framework particle structure combined with the carbon fiber surface can form an uneven rough surface structure through its extremely low surface energy and surface roughness effect, thereby not only promoting the internal absorption effect of the framework particles on water molecules when the sponge contacts water molecules, but also greatly reducing the formation rate of the hydration layer on the sponge surface when on the surface, reducing the activity of active molecules inside, and enhancing the intermolecular steric hindrance, thereby obtaining excellent waterproofness and aging resistance.
[0036] As a preferred solution, the foaming agent is at least one of deionized water, cyclopentane, sodium bicarbonate, and supercritical carbon dioxide.
[0037] As a preferred solution, the foaming agent is deionized water or cyclopentane.
[0038] As a preferred solution, the flame retardant is at least one of triphenyl phosphate, tris(2-chloropropyl) phosphate, aluminum hydroxide, magnesium hydroxide, melamine, and ammonium polyphosphate.
[0039] As a preferred solution, the flame retardant is a combination of triphenyl phosphate and melamine.
[0040] As a preferred solution, the mass ratio of triphenyl phosphate to melamine is (5-7):(1.5-3).
[0041] As a preferred solution, the catalyst is at least one of triethylenediamine, dibutyltin dilaurate, ethylenediamine and triethylamine.
[0042] As a preferred solution, the catalyst is triethylenediamine.
[0043] As a preferred solution, the auxiliary agent at least includes a dispersant and an antioxidant.
[0044] As a preferred solution, the mass ratio of the dispersant to the antioxidant is (6-10):(2-4).
[0045] As a preferred solution, the dispersant is at least one of polyethylene glycol ether or C12-C13 fatty alcohol polyoxyethylene ether.
[0046] As a preferred solution, the dispersant is at least one of C12-C13 fatty alcohol polyoxyethylene ethers.
[0047] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 264, antioxidant 1076, antioxidant 5057, and antioxidant 1135.
[0048] The second aspect of the present application provides a method for preparing the above-mentioned halogen-free flame retardant sponge, and the preparation method comprises the following steps: S1: the modified filler and the modified resin are mixed and stirred at 200-300 rpm in a high-speed mixer for 30-40 minutes, and then added to a mixed solution of polyether polyol and polypropylene glycol, and mixed and stirred for a second time at 200-300 rpm for 40-45 minutes, during which the remaining raw materials except polyisocyanate and catalyst are added in sequence; S2: then the polyisocyanate and the catalyst are added and stirred at a speed of 1200-1500 rpm for 4-6 minutes, and added to the sponge mold, the mold temperature is controlled at 40-50°C, and the mold is kept warm for 12-20 hours. After completion, it is washed and cut to obtain the sponge.
[0049] The third aspect of the present application provides an application of the above-mentioned halogen-free flame retardant sponge in furniture, electronic devices, vehicle interiors, and building exteriors.
[0050] The beneficial effects of this application are:
[0051] 1. The halogen-free flame retardant sponge provided in the present application has better mechanical properties and flame retardancy, is halogen-free and more environmentally friendly; on the other hand, the halogen-free flame retardant sponge prepared in the present application can effectively improve its waterproofness, light resistance and aging resistance, etc., meet the multi-performance requirements of existing products for halogen-free flame retardant sponge, and has a very excellent market prospect.
[0052] 2. A halogen-free flame retardant sponge provided in the present application, the added modified resin can effectively improve the mechanical, waterproof, light-resistant and aging-resistant properties of the modified resin; the modified resin can produce a good cross-linking effect with polyurethane through the various groups it carries, and can act with the modified filler group in the system to become a good carrier, thereby improving the free efficiency of the modified filler in the sponge system, and after the formation of the sponge system, the dispersion effect of the modified filler is greatly enhanced, avoiding the performance degradation problem caused by excessive filler aggregation; on the other hand, the long molecular chain carried by the modified resin can greatly enhance the steric hindrance of the modified filler when it acts in the sponge system, and effectively guides the modified filler through the long molecular chain, thereby forming a barrier effect on the active molecules and reactive groups, reducing their collision and contact frequency, and thus obtaining excellent anti-photooxidation, anti-aging and other properties during long-term use.
[0053] 3. A halogen-free flame retardant sponge provided in the present application, the added modified filler can form a composite connection structure with carbon fiber as the main skeleton, the structure can form a good electron pathway through surface groups and coordination connection, extend the path of the electron pathway, thereby obtaining a good electron transport effect both under the action of light and under normal conditions, the existence of this effect can greatly enhance the transport efficiency of the sponge system for charges and electrons, so that the flame retardant sponge has excellent antistatic and light resistance.
[0054] 4. A halogen-free flame retardant sponge provided in the present application has a modified filler added thereto, and the composite structure formed by the modified filler can form a good spreading effect in the sponge system with the carbon fiber plane as the main body, thereby enhancing the dispersion uniformity and stability of the composite filler in the sponge, and can strengthen the intermolecular force between the composite filler and the sponge polymer matrix through the connection of the surface groups, thereby playing a good connection role when an external force acts; in addition, the framework particle structure combined with the carbon fiber surface can form an uneven rough surface structure through its extremely low surface energy and surface roughness effect, thereby not only promoting the internal absorption effect of the framework particles on water molecules when the sponge contacts water molecules, but also greatly reducing the formation speed of the hydration layer on the sponge surface when on the surface, reducing the activity of the active molecules inside, and enhancing the intermolecular steric hindrance, thereby obtaining excellent waterproofness and aging resistance. DETAILED DESCRIPTION
[0055] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0056] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0057] Example 1
[0058] Example 1 The first aspect provides a halogen-free flame retardant sponge, the raw materials of which are, by mass: 72.5 parts of polyether polyol, 14.5 parts of polypropylene glycol, 53.8 parts of polyisocyanate, 19.2 parts of modified resin, 15.6 parts of modified filler, 3.8 parts of foaming agent, 8.5 parts of flame retardant, 1.8 parts of catalyst, and 11.5 parts of auxiliary agent.
[0059] The polyether polyol is a composition of polyoxypropylene triol and glyceryl polyether triol, and the mass ratio of the two is 5.6:1.4.
[0060] The weight average molecular weight of polyoxypropylene triol is 4500 g / mol, and the product with the corresponding molecular weight is purchased from Suzhou Senfida Chemical Co., Ltd.
[0061] The weight average molecular weight of glyceryl polyether triol is 3000 g / mol, and the product with the corresponding molecular weight is purchased from Haian Petrochemical Company in Jiangsu Province.
[0062] The weight average molecular weight of polypropylene glycol was 1000 g / mol, and the product with the corresponding molecular weight was purchased from Haian Petrochemical Company in Jiangsu Province.
[0063] The polyisocyanate is a composition of 2,4'-diphenylmethane diisocyanate and cyclohexane diisocyanate, and the mass ratio of the two is 4.38:1.
[0064] The preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 10.5 parts of glycidyl methacrylate, 3.2 parts of isooctyl acrylate, 2.3 parts of dodecyl acrylate and 1.1 parts of benzophenone into a reaction container, irradiating with a wavelength of 350nm under nitrogen for 2 hours, filtering the precipitate after the reaction is completed, and obtaining a prepolymer; S2: uniformly mixing 25.5 parts of the prepolymer with 4.5 parts of acrylamide, 1.8 parts of malonic acid and 6.5 parts of hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into 220 parts of acetone solvent, then sequentially adding 0.16 parts of triphenylphosphine and 0.21 parts of benzoyl peroxide, heating to 80°C, stirring in a closed manner for 11.5 hours, and obtaining a preproduct; S3: mixing 9.8 parts of the preproduct with 3.1 parts of succinic anhydride and 0.78 parts of γ-aminopropyltriethoxysilane, maintaining the temperature at 55°C for 2.5 hours, filtering and washing the product after completion, and vacuum drying to obtain the product.
[0065] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.8 parts of carbon fiber and 0.55 parts of zinc oxide are mixed and added to 80 parts of DMF solvent, 1.35 parts of succinic anhydride and 0.28 parts of 3-aminopropyltriethoxysilane are added, and the temperature is raised to 65°C for insulation reaction for 3 hours, and after completion, the mixture is filtered, washed and taken out to obtain a pre-treated mixture; S2: 3.5 parts of the pre-treated mixture are added to 80 parts of DMF solvent again, and 0.75 parts of zinc nitrate hexahydrate are added at the same time to form a mixed solution, and then Then, a DMF solution containing 1.3 parts of 2,5-dihydroxyterephthalic acid (20 parts in total) is prepared in another container, and the temperature is raised to 70°C in the reactor, and the DMF solution of 2,5-dihydroxyterephthalic acid is preferentially added. After preheating evenly, the mixed solution is slowly added, accompanied by stirring at 35 rpm for 15 minutes; S3: Seal the reactor, and heat it to 135°C, stir at 80 rpm for 38 hours, and after the reaction is completed, naturally cool to room temperature, centrifuge and filter, wash the product with methanol, and vacuum dry at 90°C to obtain.
[0066] The average particle size of zinc oxide is 20 nm. The average diameter of carbon fiber is 5.5 μm and the average length is 1 mm. It is purchased from Jiangxi Shuobang New Material Technology Co., Ltd. and is sheared to the required size.
[0067] The foaming agent is deionized water; the flame retardant is a combination of triphenyl phosphate and melamine, and the mass ratio of the two is 6.5:2.
[0068] The catalyst is triethylenediamine.
[0069] The additives are dispersant and antioxidant, and the mass ratio of the two is 9.5:2.
[0070] The dispersant is isomeric C13 fatty alcohol polyoxyethylene ether, purchased from Hai'an Guoyun Chemical Co., Ltd. as model E-1304.
[0071] The antioxidant is antioxidant 1010.
[0072] The second aspect of the present embodiment provides a method for preparing the above-mentioned halogen-free flame retardant sponge, and the preparation method comprises the following steps: S1: the modified filler and the modified resin are mixed and stirred at 280 rpm in a high-speed mixer for 35 minutes, and then added to a mixed solution of polyether polyol and polypropylene glycol, and mixed and stirred for a second time at 300 rpm for 42 minutes, during which the remaining raw materials except polyisocyanate and catalyst are added in sequence; S2: thereafter, polyisocyanate and catalyst are added and stirred at a speed of 1400 rpm for 6 minutes, added to a sponge mold, the mold temperature is controlled at 45°C, and kept warm for 16 hours. After completion, the mold is washed and cut.
[0073] Example 2
[0074] Example 2 The first aspect provides a halogen-free flame retardant sponge, the raw materials of which are, by mass: 65 parts of polyether polyol, 12 parts of polypropylene glycol, 48.5 parts of polyisocyanate, 15.5 parts of modified resin, 12.2 parts of modified filler, 3.1 parts of foaming agent, 7.5 parts of flame retardant, 1.6 parts of catalyst, and 9.5 parts of auxiliary agent.
[0075] The polyether polyol is a composition of polyoxypropylene triol and glyceryl polyether triol, and the mass ratio of the two is 5:2.
[0076] The weight average molecular weight of polyoxypropylene triol is 4500 g / mol, and the product with the corresponding molecular weight is purchased from Suzhou Senfida Chemical Co., Ltd.
[0077] The weight average molecular weight of glyceryl polyether triol is 3000 g / mol, and the product with the corresponding molecular weight is purchased from Haian Petrochemical Company in Jiangsu Province.
[0078] The weight average molecular weight of polypropylene glycol was 1000 g / mol, and the product with the corresponding molecular weight was purchased from Haian Petrochemical Company in Jiangsu Province.
[0079] The polyisocyanate is a composition of 2,4'-diphenylmethane diisocyanate and cyclohexane diisocyanate, and the mass ratio of the two is 4.4:0.8.
[0080] The preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 10.5 parts of glycidyl methacrylate, 3.2 parts of isooctyl acrylate, 2.3 parts of dodecyl acrylate and 1.1 parts of benzophenone into a reaction container, irradiating with a wavelength of 350nm under nitrogen for 2 hours, filtering the precipitate after the reaction is completed, and obtaining a prepolymer; S2: uniformly mixing 25.5 parts of the prepolymer with 4.5 parts of acrylamide, 1.8 parts of malonic acid and 6.5 parts of hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into 220 parts of acetone solvent, then sequentially adding 0.16 parts of triphenylphosphine and 0.21 parts of benzoyl peroxide, heating to 80°C, stirring in a closed manner for 11.5 hours, and obtaining a preproduct; S3: mixing 9.8 parts of the preproduct with 3.1 parts of succinic anhydride and 0.78 parts of γ-aminopropyltriethoxysilane, maintaining the temperature at 55°C for 2.5 hours, filtering and washing the product after completion, and vacuum drying to obtain the product.
[0081] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.8 parts of carbon fiber and 0.55 parts of zinc oxide are mixed and added to 80 parts of DMF solvent, 1.35 parts of succinic anhydride and 0.28 parts of 3-aminopropyltriethoxysilane are added, and the temperature is raised to 65°C for insulation reaction for 3 hours, and after completion, the mixture is filtered, washed and taken out to obtain a pre-treated mixture; S2: 3.5 parts of the pre-treated mixture are added to 80 parts of DMF solvent again, and 0.75 parts of zinc nitrate hexahydrate are added at the same time to form a mixed solution, and then Then, a DMF solution containing 1.3 parts of 2,5-dihydroxyterephthalic acid (20 parts in total) is prepared in another container, and the temperature is raised to 70°C in the reactor, and the DMF solution of 2,5-dihydroxyterephthalic acid is preferentially added. After preheating evenly, the mixed solution is slowly added, accompanied by stirring at 35 rpm for 15 minutes; S3: Seal the reactor, and heat it to 135°C, stir at 80 rpm for 38 hours, and after the reaction is completed, naturally cool to room temperature, centrifuge and filter, wash the product with methanol, and vacuum dry at 90°C to obtain.
[0082] The average particle size of zinc oxide is 20 nm. The average diameter of carbon fiber is 5.5 μm and the average length is 1 mm. It is purchased from Jiangxi Shuobang New Material Technology Co., Ltd. and is sheared to the required size.
[0083] The foaming agent is deionized water; the flame retardant is a combination of triphenyl phosphate and melamine, and the mass ratio of the two is 6.5:2.
[0084] The catalyst is triethylenediamine.
[0085] The additives are dispersant and antioxidant, and the mass ratio of the two is 9.5:2.
[0086] The dispersant is isomeric C13 fatty alcohol polyoxyethylene ether, purchased from Hai'an Guoyun Chemical Co., Ltd. as model E-1304.
[0087] The antioxidant is antioxidant 1010.
[0088] The second aspect of the present embodiment provides a method for preparing the above-mentioned halogen-free flame retardant sponge, and the preparation method comprises the following steps: S1: the modified filler and the modified resin are mixed and stirred at 280 rpm in a high-speed mixer for 35 minutes, and then added to a mixed solution of polyether polyol and polypropylene glycol, and mixed and stirred for a second time at 300 rpm for 42 minutes, during which the remaining raw materials except polyisocyanate and catalyst are added in sequence; S2: thereafter, polyisocyanate and catalyst are added and stirred at a speed of 1400 rpm for 6 minutes, added to a sponge mold, the mold temperature is controlled at 45°C, and kept warm for 16 hours. After completion, the mold is washed and cut.
[0089] Comparative Example 1
[0090] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the halogen-free flame retardant sponge, in parts by mass, are: 72.5 parts of polyether polyol, 14.5 parts of polypropylene glycol, 53.8 parts of polyisocyanate, 15.8 parts of modified resin, 5.8 parts of modified filler, 3.8 parts of foaming agent, 8.5 parts of flame retardant, 1.8 parts of catalyst, and 11.5 parts of auxiliary agent.
[0091] Comparative Example 2
[0092] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the halogen-free flame retardant sponge, in parts by mass, are: 72.5 parts of polyether polyol, 14.5 parts of polypropylene glycol, 53.8 parts of polyisocyanate, 8.5 parts of modified resin, 16 parts of modified filler, 3.8 parts of foaming agent, 8.5 parts of flame retardant, 1.8 parts of catalyst, and 11.5 parts of additives.
[0093] Comparative Example 3
[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: 15.5 parts of glycidyl methacrylate, 1.5 parts of isooctyl acrylate, 1.1 parts of dodecyl acrylate and 0.9 parts of benzophenone are added into a reaction container and irradiated with nitrogen at a wavelength of 350 nm for 2 hours. After the reaction is completed, the precipitate is filtered to obtain a prepolymer; S2: 25.5 parts of the prepolymer are mixed with 4.5 parts of acrylamide, 1 .8 parts of malonic acid and 6.5 parts of hydroxymethyl bisphenol A diglycidyl ether are evenly mixed and added to 220 parts of acetone solvent, followed by adding 0.16 parts of triphenylphosphine and 0.21 parts of benzoyl peroxide in sequence, and the temperature is raised to 80°C and stirred in a closed manner for 11.5 hours to obtain a pre-product; S3: 9.8 parts of the pre-product are mixed with 3.1 parts of succinic anhydride and 0.78 parts of γ-aminopropyltriethoxysilane, and the temperature is maintained at 55°C for 2.5 hours. After completion, the product is filtered, washed, and vacuum dried to obtain.
[0095] Comparative Example 4
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: 10.5 parts of glycidyl methacrylate, 3.2 parts of isooctyl acrylate, 2.3 parts of dodecyl acrylate and 1.1 parts of benzophenone are added into a reaction container and irradiated with nitrogen at a wavelength of 350nm for 2h. After the reaction is completed, the precipitate is filtered to obtain a prepolymer; S2: 38.5 parts of the prepolymer and 3.5 parts of acrylamide, 1 .4 parts of malonic acid and 5.5 parts of hydroxymethyl bisphenol A diglycidyl ether are evenly mixed and added to 260 parts of acetone solvent, followed by adding 0.19 parts of triphenylphosphine and 0.24 parts of benzoyl peroxide in sequence, and the temperature is raised to 80°C and stirred in a closed manner for reaction for 11.5 hours to obtain a pre-product; S3: 9.8 parts of the pre-product are mixed with 3.1 parts of succinic anhydride and 0.78 parts of γ-aminopropyltriethoxysilane, and the temperature is maintained at 55°C for reaction for 2.5 hours. After completion, the product is filtered, washed, and vacuum dried to obtain.
[0097] Comparative Example 5
[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.8 parts of carbon fiber and 0.55 parts of zinc oxide are mixed and added to 100 parts of deionized water, 0.55 parts of 3-aminopropyltriethoxysilane and the temperature is raised to 65°C for insulation reaction for 3 hours, after completion, filtered, washed and taken out to obtain a pre-treated mixture; S2: 3.5 parts of the pre-treated mixture are added again to 80 parts of DMF solvent, and 0.75 parts of hexahydrate nitric acid are added at the same time Zinc forms a mixed solution, and then a DMF solution containing 1.3 parts of 2,5-dihydroxyterephthalic acid (20 parts in total) is prepared in another container, the temperature is raised to 70°C in the reactor, and the DMF solution of 2,5-dihydroxyterephthalic acid is preferentially added. After preheating evenly, the mixed solution is slowly added, accompanied by stirring at 35rpm for 15min; S3: the reactor is sealed, and the temperature is raised to 135°C, and the reaction is stirred at 80rpm for 38h. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, the product is washed with methanol, and vacuum dried at 90°C to obtain.
[0099] Comparative Example 6
[0100] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 4.5 parts of carbon fiber and 0.15 parts of zinc oxide are mixed and added to 80 parts of DMF solvent, 1.45 parts of succinic anhydride and 0.35 parts of 3-aminopropyltriethoxysilane are added, and the temperature is raised to 65°C and kept for reaction for 3 hours. After completion, the mixture is filtered, washed and taken out to obtain a pre-treated mixture; S2: 3.5 parts of the pre-treated mixture are added again to 80 parts of DMF solvent, and 0.7 5 parts of zinc nitrate hexahydrate to form a mixed solution, then prepare a DMF solution containing 1.3 parts of 2,5-dihydroxyterephthalic acid (20 parts in total) in another container, heat it to 70°C in the reactor, add the DMF solution of 2,5-dihydroxyterephthalic acid first, preheat evenly and then slowly add the mixed solution, stirring at 35 rpm for 15 min; S3: seal the reactor, heat it to 135°C, stir at 80 rpm for 38 h, cool it naturally to room temperature after the reaction is completed, centrifuge and filter, wash the product with methanol, and dry it in a vacuum oven at 90°C to obtain the product.
[0101] Comparative Example 7
[0102] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.8 parts of carbon fiber and 0.55 parts of zinc oxide are mixed and added to 80 parts of DMF solvent, 1.35 parts of succinic anhydride and 0.28 parts of 3-aminopropyltriethoxysilane are added, and the temperature is raised to 65°C and kept for reaction for 3 hours. After completion, the mixture is filtered, washed and taken out to obtain a pre-treated mixture; S2: 3.5 parts of the pre-treated mixture are added again to 80 parts of DMF solvent, and 0.35 parts of succinic anhydride and 0.28 parts of 3-aminopropyltriethoxysilane are added at the same time. parts of zinc nitrate hexahydrate to form a mixed solution, and then a DMF solution containing 0.82 parts of 2,5-dihydroxyterephthalic acid (15 parts in total) is prepared in another container, the temperature is raised to 70°C in the reactor, and the DMF solution of 2,5-dihydroxyterephthalic acid is preferentially added. After preheating evenly, the mixed solution is slowly added, accompanied by stirring at 35 rpm for 15 minutes; S3: the reactor is sealed, and the temperature is raised to 135°C, and the reaction is stirred at 80 rpm for 38 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, the product is washed with methanol, and vacuum dried at 90°C to obtain.
[0103] Comparative Example 8
[0104] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 40 nm; the average diameter of carbon fiber is 8.5 μm, and the average length is 3.2 mm, which are purchased from Jiangxi Shuobang New Material Technology Co., Ltd.
[0105] Performance Evaluation
[0106] Flame retardant properties: The flame retardant sponges prepared in the examples and comparative examples were subjected to flame retardant tests with reference to standard GB / T8624-2012, and the flame retardant grade results are recorded in Table 1.
[0107] Waterproof performance: The flame retardant sponges prepared in the embodiments and comparative examples were used to prepare 2cm×2cm×1cm samples, and the water contact angle on their surfaces was tested by the sessile drop method. The test water drop size was 2.5 μL, and the test time was 10 s. The water contact angle at 10 s was calculated, and the test was continued until the water drop was completely immersed in the polyurethane sponge. The immersion time (s) was recorded, and the test value was the average of 10 tests and recorded in Table 1.
[0108] Light resistance: The flame retardant sponges prepared in the examples and comparative examples were placed in a test box with sufficient light, and sufficient light was maintained for 8 hours per day at room temperature of 25-35°C, for a total of 180 days of light exposure. After the test, the sponges were observed to see if they had yellowing or oxidation aging due to light exposure. 50 samples were tested in each group, and the sample pass rate was recorded in Table 1.
[0109] Aging resistance: The flame retardant sponges prepared in the examples and comparative examples were placed in a constant temperature and humidity chamber at a temperature of 65°C and a relative humidity of 75% for 6 months. After 6 months, they were taken out and observed for yellowing, oxidation, breakage and cracking. If so, they were recorded as unqualified, otherwise they were qualified. 50 samples were tested in each group, and the sample qualification rate was recorded in Table 1.
[0110] Table 1 Performance test results
[0111]
[0112] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of light resistance, waterproof performance and aging resistance. This is mainly due to the combined effect of the modified resin and modified filler added as specified in the present application. Comparative examples 1 to 8 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A halogen-free flame retardant sponge, characterized in that: The raw materials are as follows, by mass: 60-80 parts of polyether polyol, 10-20 parts of polypropylene glycol, 40-60 parts of polyisocyanate, 10-25 parts of modified resin, 10-20 parts of modified filler, 2-5 parts of foaming agent, 5-10 parts of flame retardant, 1-3 parts of catalyst, and 5-15 parts of auxiliary agent; The mass ratio of the polyether polyol, polypropylene glycol and polyisocyanate is (6.5-8): (1.2-1.8): (4.5-5.5); The polyether polyol is a composition of polyoxypropylene triol and glyceryl polyether triol; the mass ratio of the polyoxypropylene triol and the glyceryl polyether triol is (5-6): (1-2); The weight average molecular weight of the polyether polyol is 2000-6000 g / mol; The weight average molecular weight of the polypropylene glycol is 1000-2000 g / mol; The polyisocyanate is at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and cyclohexane diisocyanate; The preparation method of the modified resin comprises the following steps: S1: adding glycidyl methacrylate, isooctyl acrylate, dodecyl acrylate and benzophenone into a reaction container, irradiating with a wavelength of 300-450nm under nitrogen for reaction for 1.5-3h, filtering the precipitate after the reaction is completed, and obtaining a prepolymer; S2: uniformly mixing the prepolymer with acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into an acetone solvent, then sequentially adding triphenylphosphine and benzoyl peroxide, heating to 75-85°C, stirring in a closed manner for reaction for 8-12h, and obtaining a preproduct; S3: mixing the preproduct with succinic anhydride and a silane coupling agent, maintaining the temperature at 50-60°C for reaction for 2-3h, filtering and washing the product after completion, and vacuum drying to obtain the product; The mass ratio of glycidyl methacrylate, isooctyl acrylate and dodecyl acrylate is (8-12): (3-4): (2-2.5); The mass ratio of the prepolymer, acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether is (22-28): (4-6): (1.5-2): (6-8).
2. The halogen-free flame retardant sponge according to claim 1, characterized in that: The mass ratio of the polyether polyol, the modified resin and the modified filler is (6.5-8): (1.5-2.2): (1.2-1.6).
3. The halogen-free flame retardant sponge according to claim 2, characterized in that: The weight average molecular weight of the polyoxypropylene triol is 4000-5000 g / mol.
4. The halogen-free flame retardant sponge according to claim 3, characterized in that: The weight average molecular weight of the glyceryl polyether triol is 2500-3500 g / mol.
5. The halogen-free flame-retardant sponge according to claim 4, characterized in that: The polyisocyanate is a composition of 2,4'-diphenylmethane diisocyanate and cyclohexane diisocyanate; the mass ratio of the 2,4'-diphenylmethane diisocyanate to the cyclohexane diisocyanate is (4-4.5): (0.5-1.5).
6. The halogen-free flame-retardant sponge according to claim 5, characterized in that: The preparation method of the modified filler comprises the following steps: S1: adding carbon fiber and zinc oxide to a DMF solvent, adding succinic anhydride and 3-aminopropyltriethoxysilane, heating to 60-70°C, and keeping the temperature for reaction for 3-3.5 hours. After completion, filtering, washing, and taking out the pretreated mixture; S2: adding the pretreated mixture to the DMF solvent again, adding zinc nitrate hexahydrate to form a mixed solution, and then preparing a DMF solution of 2,5-dihydroxyterephthalic acid in another container, heating the temperature in a reactor to 60-80°C, preferentially adding the DMF solution of 2,5-dihydroxyterephthalic acid, preheating evenly, and slowly adding the mixed solution, accompanied by stirring at 30-40 rpm for 10-15 minutes; S3: sealing the reactor, heating the temperature to 130-145°C, stirring at 60-80 rpm for reaction for 30-42 hours, cooling naturally to room temperature after the reaction is completed, centrifuging, washing the product with methanol, and vacuum drying at 80-90°C to obtain the filler.
7. The halogen-free flame retardant sponge according to claim 6, characterized in that: The mass ratio of the carbon fiber, zinc oxide, succinic anhydride and 3-aminopropyltriethoxysilane is (3-4): (0.4-0.6): (1.2-1.5): (0.2-0.3).
8. The halogen-free flame-retardant sponge according to claim 7, characterized in that: The mass ratio of the pretreatment mixture, zinc nitrate hexahydrate and 2,5-dihydroxyterephthalic acid is (3.5-3.8): (0.7-0.8): (1.2-1.4).
9. A method for preparing a halogen-free flame retardant sponge according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: mixing and stirring the modified filler and the modified resin in a high-speed mixer at 200-300 rpm for 30-40 minutes, and then adding the mixture into a mixed solution of polyether polyol and polypropylene glycol, and mixing and stirring for a second time at 200-300 rpm for 40-45 minutes, during which the remaining raw materials except polyisocyanate and the catalyst are added in sequence; S2: then adding the polyisocyanate and the catalyst and stirring at a speed of 1200-1500 rpm for 4-6 minutes, adding the mixture into a sponge mold, controlling the mold temperature at 40-50°C, and keeping the temperature for 12-20 hours, and washing and cutting the mixture after completion to obtain the sponge.
10. Use of the halogen-free flame retardant sponge according to any one of claims 1 to 8 in furniture, electronic devices, vehicle interiors, and building exteriors.
Citation Information
Patent Citations
Flame-retardant polyurethane soft sponge and preparation method thereof
CN110951021A
Flame-retardant sponge and preparation method thereof
CN113444218A